Microstructural, trace element and geochronological characterization of TiO2 polymorphs and implications for mineral exploration - Plavsa, D.; Reddy, Steven; Agangi, Andrea; Clark, Christopher; Kylander-Clark, A.; Tiddy, C. (Elsevier Science BV, 2018)
The geochemistry of rutile (TiO 2 ) has recently found its use in mineral exploration with some studies reporting anomalous concentrations of Fe, W, V, Sn and Sb in rutile associated with mineralized ore systems. However, the use of rutile as a prospecting tool is likely to be complicated by the systematic changes in trace element composition with TiO 2 polymorph type (anatase, brookite and rutile). Here we present TiO 2 trace element and U–Pb geochronological data from the mineralized and barren portions of the Palaeoproterozoic Moorarie Supersuite and (Capricorn Orogen, Western Australia), with a focus on the Minnie Creek Molybdenum Prospect in the northern part of the Gascoyne Province. The barren samples contain all three TiO 2 polymorphs (anatase, brookite and rutile). Textures suggest anatase and brookite may have formed during low-T metamorphism, either through replacement of previous rutile grains or titaniferous minerals. Rutile grains from barren samples yield variable U–Pb ages (ca. 3.0–2.2 Ga) as well as variable textures and chemical compositions suggesting detrital origins, thus most likely representing metasedimentary units intruded by the Moorarie Supersuite. Rutile grains from the Minnie Creek prospect yield Palaeoproterozoic (ca. 1.77–1.75 Ga) U–Pb cooling ages and Nb + Ta concentrations of up to 17 wt% that along with inclusions of manganocolumbite, oscillatory and patchy zonation of Nb and Fe, suggest a magmatic origin. The commonly used pathfinder elements for gold and base-metal mineralisation (Fe, Cr, V, W, Sn and Sb) are shown to be systematically lower in anatase and brookite, thus yielding false negatives if polymorph type is not identified during reconnaissance studies. For this reason, a ternary diagram was constructed based on the systematic changes in chemistry of TiO 2 polymorphs to provide a relatively fast and easy chemical discrimination of polymorphs in large volumes of reconnaissance data. Furthermore, it is shown that high Al concentrations are characteristic of brookite and, to a lesser degree, anatase but not rutile. In addition, Sn, Nb, Ta and W concentrations in rutile may be more sensitive to igneous processes and may be used to track processes occurring in strongly fractionated granitic magmas such as pegmatites and associated deposits.